Effect of Quantum Dots Density and temperature on Quantum Dot Laser Characteristics - Hassan, Ra'ed M. (University of Thi-Qar Journal of Science, 2014)
Detailed theoretical study of the effects of surface density of quantum dots on the dynamics of quantum dot lasers (QDLs) is given. Temperature dependence of the threshold current density, confined level occupancy, internal loss coefficient, optical confinement layer (OCL), characteristic temperature and lowest excitation energy with the variation of internal loss constant component, root mean square of relative QD–size fluctuations, mean size of QDs and optical confinement factor are studied.